An investigation into the linguistic landscape of translingual storybooks for Arabic-English bilingual children. Issue 4 (20th April 2020) - Gallagher, Kay; Bataineh, Afaf
ABSTRACT: This study investigates the linguistic landscape of eight culturally-responsive, translingual picture storybooks written by bilingual Arabic-English teacher candidates for young emergent bilingual children. Drawing on linguistic content analysis methodology, the study analyses the cross-linguistic challenges teacher candidates faced in creating translingual children's story books for young Emirati children wherein Arabic and English are meshed, and examines the strategies they used to integrate the two linguistic systems. The study also examines what the storybooks convey, explicitly or implicitly, about culture and language in the UAE where the storybooks were created. The findings of the paper indicate that meshing Arabic and English is not a simple undertaking and that directionality, linguistic balance, page layout, name selections, environmental print and cultural content are impacted by this process of meshing. As prototypes, however, these storybooks have yielded valuable educational lessons.